Increasing Website Browsing Efficiency Using The User Centered Design Approach At The STMIK Syaikh Zainuddin NW - Siska, Siska Atmawan Oktavia; Alfan Habib, Muhammad (Management of Information System Journal, 2025)
Educational institution websites are required to continue to make improvements and adjustments both in the content of the content that is loaded on the website as well as new things needed by its users. The lack of visitors visiting the STMIK campus website Syaikh Zainuddin NW Anjani is a problem for the Institute. Therefore this research focuses on how to develop the SMTIK NW Anjani website to increase the number of visitors. As a medium that is used to promote the campus, of course the website must be made better both in terms of interface design and in terms of content presentation in accordance with user involvement. Website analysis and evaluation is carried out to develop a system. Improvements made based on the results of data analysis using the User Centred Design method. This study uses the User-centred Design method which in its development uses the user's perspective of the system. The discussion of this research starts from identifying user needs, analysing user needs, evaluating initial designs, creating solution designs, and evaluating solution designs. so that the display or information provided is in accordance with user needs and provides information that is always updated and can help in the teaching and learning process. The results of the evaluation analysis can be used to redesign the interface of the site https://stmiksznw.ac.id/. The discussion of this research starts from identifying user needs, analysing user needs, evaluating initial designs, creating solution designs. After analysing data to see the percentage level effectiveness, efficiency and level of satisfaction felt by users when using the initial website and the proposed website. Data is then used as a basis for making improvements made in the prototyping paper as a proposed website.